2011
DOI: 10.1175/jpo-d-11-06.1
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Quasigeostrophic Oceanic Vortices to Tropical Cyclone Forcing

Abstract: The response of quasigeostrophic (QG) oceanic vortices to tropical cyclone (TC) forcing is investigated using an isopycnic ocean model. Idealized oceanic currents and wind fields derived from observational data acquired during Hurricane Katrina are used to initialize this model. It is found that the upwelling response is a function of the curl of wind-driven acceleration of oceanic mixed layer (OML) currents rather than a function of the wind stress curl. Upwelling (downwelling) regimes prevail under the TC's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…Point (2) reflects the assumption about the importance of the asymmetric cross-track thermal response compared to along-track directions, which has been noted in numerous previous case studies (Black and Dickey, 2008;Deal, 2011;Price et al, 2008). However, recent studies (Jaimes and Shay, 2010;James et al, 2011) suggest ocean variability along the track can substantially modulate the ocean cooling response to TC forcing and distort the temperature anomaly in the wake of the storm, which can be important within western boundary currents and associated geostrophic vortices. As a first step to determining TC effects on upper ocean thermal structure on a global scale, we focus primarily on the cross-track ocean response.…”
Section: Cheng Et Al: Tropical Cyclone-induced Ocean Thermal Chanmentioning
confidence: 88%
See 1 more Smart Citation
“…Point (2) reflects the assumption about the importance of the asymmetric cross-track thermal response compared to along-track directions, which has been noted in numerous previous case studies (Black and Dickey, 2008;Deal, 2011;Price et al, 2008). However, recent studies (Jaimes and Shay, 2010;James et al, 2011) suggest ocean variability along the track can substantially modulate the ocean cooling response to TC forcing and distort the temperature anomaly in the wake of the storm, which can be important within western boundary currents and associated geostrophic vortices. As a first step to determining TC effects on upper ocean thermal structure on a global scale, we focus primarily on the cross-track ocean response.…”
Section: Cheng Et Al: Tropical Cyclone-induced Ocean Thermal Chanmentioning
confidence: 88%
“…2a and b). It is also possible that instantaneous wind erosion plays a role in addition to upwelling (Jacob and Shay, 2003;James et al, 2011) for the upper ocean changes (upper 200 m), in particular during slower storms that produce weaker nearinertial velocity responses. Despite smoothing out of inertial oscillations, the resultant subsurface warming is observable.…”
Section: The 0-3-day Footprint Of Ocean Thermal Changesmentioning
confidence: 99%
“…Measurements of Jaimes and Shay [2009] demonstrated that both Hurricanes Katrina and Rita lost strength over lowest SST regions, within TC-intensified CCEs along their tracks. Case studies in other ocean basins have supported these findings using observations and models [Emanuel, 1999;Goni and Trinanes, 2003;Halliwell et al, 2008;Zheng et al, 2008Zheng et al, , 2010Jaimes et al, 2011;Lin et al, 2005Lin et al, , 2009aLin et al, , 2013.…”
Section: Introductionmentioning
confidence: 85%
“…Many of these mesoscale features are associated with the Kuroshio rings (Yasuda et al, 1992) or are a result of the instability of the shear flow between the westward North Equatorial Current and the eastward Subtropical Countercurrent (Qiu, 1999;Roemmich & Gilson, 2001). In a recent study, Jaimes et al (2011) found that an upwelling (downwelling) regime prevails under a tropical cyclone's eye as it translates over cold (warm) mesoscale features. It has been suggested that the mesoscale features are a critical condition for typhoon intensification (Lin et al, 2008) and are important for accurately simulating the ML cooling induced by tropical cyclones (Jaimes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Jaimes et al (2011) found that an upwelling (downwelling) regime prevails under a tropical cyclone's eye as it translates over cold (warm) mesoscale features. It has been suggested that the mesoscale features are a critical condition for typhoon intensification (Lin et al, 2008) and are important for accurately simulating the ML cooling induced by tropical cyclones (Jaimes et al, 2011). Using Argo profiles to study the response of the upper ocean to typhoons must take into account the influence of these features.…”
Section: Introductionmentioning
confidence: 99%